Control of a servo-hydraulic platform using parallel kinematics for incremental forming - Bastos, Nuno Ricardo Pereira (2018)
SPIF-A is an innovative project about Gough-Stewart platform using parallel kinematics for incremental forming that is supported by different fields of engineering. It is a long term work composed by a professional team that includes professors, students and researchers fancying to improve and contribute for scientific knowledge. Incremental forming is emerging due to its useful advantages, highlighting the high-speed machining. The objective is the control of a Gough-Stewart platform, planning and execution of G-code trajectories. Thereunto, a state-of-the-art regarding incremental forming, parallel platforms, parallel kinematics and control theory is carried out. Position controllers and trajectory planning are developed and implemented for a 6 degree-of-freedom manipulator. Accuracy and reliability tests are done to consummate an hardware improvement. Some types of controllers, based in fuzzy logic and one linear PID, were studied and executed on this platform in order to improve its control system.